'Risky Business': Disease, Disaster and the Unintended Consequences of Epizootics in Eighteenth- and Nineteenth-Century France and Germany. (1st February 2011) - Brantz, Dorothee
Abstract : Livestock diseases have a long history. Epizootics like cattle plague and foot and mouth disease have always been a great threat to the well being of animals, human health, and agricultural production. However, thus far they have received little attention in the historical scholarship on risk management. The following essay seeks to contribute to this scholarship by looking at the history of Rinderpest in eighteenth and nineteenth century France and Germany. In comparing these two examples, the essay examines how epizootics have affected the development of European meat production. I maintain that they fostered the creation of expert knowledge, which in turn directly affected the reform of meat production. Yet it also increased the realization that meat production always remained a risky business prone to such 'natural' disasters.